Reconhecimento de cores de objetos e de alimentos de cromaticidades opostas por pintos de corte - Fernandes, D.P.B.; Silva, I.J.O.; Nazareno, A.C.; Donofre, A.C.; Sevegnani, K.B. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2015)
The aim of this research was to evaluate, by preference tests, the ability of perception of broiler chicks in the recognition of objects and foods of different colors. The survey was conducted in Brazil and consisted in the conditioning of 60 sexed one-day-old chicks using 30 male chicks and 30 female chicks for three days with blue balls and red food colors chosen for having opposed chromaticities. After the conditioning phase, a preference test was performed, in which the animals were placed individually in the center of an arena test with four options: red food, blue food, red balls and blue balls. Each bird was measured for 10 minutes. Latency to the first peck and the number of pecks, the number of sequential pecks at each object type or food, the total time the bird in each occupied compartment and the first occupied slot were recorded. According to the results, female chicks are less inhibited when in contact with a new situation when compared with males. However, males were able to establish a standard environment in the conditioning phase and opted for the compartment which was closer to that situation, associating the blue color to the ball and red color to the food. Overall, among the types of object colors and between types of food colors, the birds took less time for the decision on the choice of blue food and blue ball, showing a greater attraction, at first, to this color. Between the two ball colors, shorter latency period, greater number of interactions as well as more time spent on site were related to the blue sphere, verifying greater preference for this object. When evaluating the types of food colors, it was observed that the highest averages related to the number of pecks, and sequential pecks occurred with red food. Therefore, it is concluded that the birds recognized the red and blue food object, with the blue color having greater attractiveness for broiler chicks when compared to red.

Objetivou-se com esta pesquisa avaliar, por meio de testes de preferência, a capacidade de percepção de pintos de corte no reconhecimento de objetos e alimentos de diferentes cores. A pesquisa foi realizada no Brasil e consistiu no condicionamento de 60 pintos de um dia sexados, sendo 30 pintos machos e 30 pintos fêmeas, durante três dias, com esferas azuis e alimento vermelho, cores escolhidas por terem cromaticidades opostas. Após a fase de condicionamento, foi realizado um teste de preferência, no qual os animais eram colocados individualmente no centro de uma arena de teste com quatro opções, sendo elas: alimento vermelho; alimento azul; esferas vermelhas; esferas azuis. Cada ave foi avaliada durante 10 minutos. Foram registrados: o período de latência para a primeira bicada; o número de bicadas; a quantidade de bicadas sequenciais em cada tipo de objeto ou alimento; o tempo total da ave em cada compartimento ocupado e o primeiro compartimento ocupado. De acordo com os resultados, pintos fêmeas são menos inibidas quando em contato com uma nova situação em relação aos machos. Entretanto, os machos foram capazes de estabelecer um padrão de ambiente na fase de condicionamento e optaram pelo compartimento que estava mais próximo daquela situação associando, da maneira correta, a cor azul à esfera e a cor vermelha ao alimento. No geral, entre os tipos de cores de objetos e entre os tipos de cores de alimentos, as aves demoraram menos tempo para a decisão da escolha do alimento e da esfera azul, evidenciando-se maior atração, em um primeiro momento, por objetos ou alimentos dessa cor. Entre as duas cores de esferas, menor período de latência, maior número de interações, bem como maior tempo de permanência no local estiveram relacionados à esfera azul, verificando-se total preferência por esse objeto. Ao avaliar os tipos de cores de alimentos, foi possível observar que as maiores médias relacionadas ao número de bicadas e de bicadas sequenciais ocorreram com o alimento vermelho. Conclui-se, portanto, que as aves reconheceram o alimento vermelho e o objeto azul, sendo a cor azul a de maior atratividade para pintos de corte em relação à vermelha.
Recognition of colors of objects and food opposite chromaticities by broiler chicks
Keywords: Animal cognition; Object recognition; Conditioning; Color perception; Cognição animal; Reconhecimento de objetos; Condicionamento; Percepção de cores